Therapeutic efficacy of a potent anti-Venezuelan equine encephalitis virus antibody is contingent on Fc effector function - Jennifer L. Schwedler; Maxwell A. Stefan; Christine E. Thatcher; Peter R. McIlroy; Anupama Sinha; Ashlee M. Phillips; Christopher A. Sumner; Colleen M. Courtney; Christina Y. Kim; Dina R. Weilhammer; Brooke Harmon (mAbs)
The development of specific, safe, and potent monoclonal antibodies (Abs) has led to novel therapeutic options for infectious disease. In addition to preventing viral infection through neutralization, Abs can clear infected cells and induce immunomodulatory functions through engagement of their crystallizable fragment (Fc) with complement proteins and Fc receptors on immune cells. Little is known about the role of Fc effector functions of neutralizing Abs in the context of encephalitic alphavirus infection. To determine the role of Fc effector function in therapeutic efficacy against Venezuelan equine encephalitis virus (VEEV), we compared the potently neutralizing anti-VEEV human IgG F5 (hF5) Ab with intact Fc function (hF5-WT) or containing the loss of function Fc mutations L234A and L235A (hF5-LALA) in the context of VEEV infection. We observed significantly reduced binding to complement and Fc receptors, as well as differential in vitro kinetics of Fc-mediated cytotoxicity for hF5-LALA compared to hF5-WT. The in vivo efficacy of hF5-LALA was comparable to hF5-WT at −24 and + 24 h post infection, with both Abs providing high levels of protection. However, when hF5-WT and hF5-LALA were administered + 48 h post infection, there was a significant decrease in the therapeutic efficacy of hF5-LALA. Together these results demonstrate that optimal therapeutic Ab treatment of VEEV, and possibly other encephalitic alphaviruses, requires neutralization paired with engagement of immune effectors via the Fc region.